STRATEGI PENINGKATAN KOMPETENSI SDM TERHADAP DAYA SAING PT POS INDONESIA - Agus Sulaksana (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2008)
Company’s human resource competence development is undoubtedly required to increase the competitiveness of the Indonesian Postal Service company. As a state-owned company, it performs its services in accordance with the Government Regulation Number 12 Year 1998, i.e. providing high quality services both in domestic and international scales. In addition to developing profits, it serves public services as authorized by the government.